Imagine - Lester, Alison (Boston : Houghton Mifflin, 1990)
Invites the reader to imagine what it would be like to live in various locations, such as a house, a jungle, and an icecap, and meet the animals that live there.
4.4
K-3.
K-3
Keywords: Animals -- Habitations -- Fiction; Imagination -- Fiction; Stories in rhyme; Animals -- Habitations -- Fiction; Imagination -- Fiction; Stories in rhyme